THE AUTONOMOUS LEARNING IN IMPROVING THE FOUR LANGUAGE SKILLS DONE BY THE BEST STUDENTS OF STMIK AMIKOM AND AKBA SINEMA YOGYAKARTA - Marita Nurharjanti (STKIP PGRI Lubuklinggau, 2018)
This research was to describe the autonomous learning of the ten best students of STMIK Amikom and AKBA Sinema Yogyakarta. Big classes were not sufficient for everyone to learn maximally. This hindrance made some students to be more creative in improving their four language skills of English by automomous learning. The study was categorized as a descriptive qualitative research. The writer uses documentation, observation, in-depth interview, data triangulation and open questionnaire methods and to analyze the data, the writer uses constant comparative study. The results were that first, the students improved listening from news and interview programs on TV and radio, music and films from their private collections such as CD, DVD, cassette or learning from the family member. Second, they improved reading from text, book, novel, newspaper and film/ song text. Third, they improved speaking by oral repeating from song and film, taking part in debating activities or competitions, making conversation in working place or in the organization, and delivering speech. Fourth, they improved writing by writing emails, composing story, writing articles and diary. Fifth, in translation, they used internet because of the time efficiency and also dictionary.